Quality of Nursing Work Life (QNWL) in Indonesia: Scoping Review - Agusto, Nyoman Wigo; Leo, Kadek Agus; Septianita, Nisa EKa (Indonesian Journal of Global Health Research, 2024)
QNWL must continue to be considered to improve the welfare of nurses, especially during the COVID-19 pandemic. The purpose of this study was to determine the description and factors associated with QNWL in Indonesia. This research is a Scoping Review, namely the identification of articles through 3 databases including Google Scholer, Science Direct and Pubmed with the keywords "Quality of Nursing Work-life" AND "Hospital" AND "Public Health Center". The inclusion criteria for the article are published in 2017-2022, full text, research in Indonesia Hospitals/Puskesmas, DOI/ISSN, quantitative research and discusses the quality of working life of nurses. The search identified 320 articles and 12 articles were selected for analysis. The results showed that the QNWL both in the Hospital/Puskesmas on average were in the sufficient/moderate/moderate category. Then, there is a significant relationship between job satisfaction, marital status, nurse performance, education, number of teams and salary/income, quality of life/quality of life during the COVID-19 pandemic with QNWL. Preferably, the management of the Hospital/Puskesmas continues to improve QNWL to improve the welfare of nurses so that they can provide optimal services.